A survey on requirements elicitation for computer-supported collaborative learning (cscl) application development among software developers - a Malaysian perspective - Kasirun, Z.M.; Salim, S.S. (2002)
ABSTRACT: Requirements elicitation has been studied in Software Engineering field to acquire as many requirements as possible for the development of an application including Computer-Supported Collaborative Learning (CSCL). These requirements are gathered using many requirements elicitation techniques such as discussions, interviews and meetings. These user requirements are recorded in a documentation called draft of user requirements document (URD). The paper suggests that development of an application should be based on complete draft of URD. The complete of URD depends on several requirements elicitation factors. The paper investigates requirements elicitation factors from several aspects namely tools, time, techniques, people, communications, processes and documents. The study discusses these factors which provides insights for devising group requirements elicitation tool, which allows the user involvement to support requirements elicitation activity. We hoped that the tool can be an effective aid of requirements elicitation activity that will produce complete draft of URD.